Creación de una línea de abrigos, incorporando técnicas artesanales y de bordado - López Vásconez, Eduarda Anahí (2024)
The present project focuses on the preservation of craft and embroidery techniques that will be reflected in a collection of women's and men's coats, which seeks to create a complementary composition of several craft techniques, exposing them as a mechanism of non-verbal communication and identity. the Andean peoples. A garment is exhibited that prevails over time by being timeless and contemporary, that maintains sustainable characteristics by using environmentally friendly materials such as alpaca fiber, cotton fabric and managing a responsible traceability process. The line of coats seeks to transmit the identity and evolution of the people through the materials and techniques used in the development of the collection, that is, the process of obtaining raw materials such as alpaca fiber, the spinning process and weaving made by the artisan women of the communities. On the other hand, this project seeks to strengthen national trade in the textile area and promote the social and economic development of small communities located in the mountain sector of Ecuador, through training that helps expand the knowledge of artisans, with the aim of vitalizing their source of inspiration when producing a garment, these being the tools to create a sustainable and identity product. This integrative project inspires future researchers to explore ancestral techniques that, in addition to being part of a sustainable process, help the economic and social development of Andean communities and the protection of the ancestral culture and traditions that have remained over time. Likewise, it is a fundamental part of innovation processes within clothing and textile exploration since materials and weaving techniques can be part of sustainable textiles.